Enhanced Sensitivity of Silicon-Photonics-Based Ultrasound Detection via BCB Coating - Resmi Ravi Kumar; Evgeny Hahamovich; Shai Tsesses; Yoav Hazan; Assaf Grinberg; Amir Rosenthal (IEEE Photonics Journal, 2019)
Ultrasound detection via silicon waveguides relies on the ability of acoustic waves to modulate the effective refractive index of the guided modes. However, the low photo-elastic response of silicon and silica limits the sensitivity of conventional silicon-on-insulator sensors, in which the silicon core is surrounded by a silica cladding. In this paper, we demonstrate that the sensitivity of silicon waveguides to ultrasound may be significantly enhanced by replacing the silica over-cladding with bisbenzocyclobutene (BCB)—a transparent polymer with a high photo-elastic coefficient. In our experimental study, the response to ultrasound, in terms of the induced modulation in the effective refractive index, achieved for a BCB-coated silicon waveguide with TM polarization was comparable to values previously reported for polymer waveguides and an order of magnitude higher than the response achieved by an optical fiber. In addition, in our study, the susceptibility of the sensors to surface acoustic waves and reverberations was reduced for both TE and TM modes when the BCB over-cladding was used.